Criopreservação de tecido somático e obtenção de linhagens fibroblásticas derivadas do pavilhão auricular de onça-parda, puma concolor (linnaeus, 1771) - Lira, Gabriela Pereira de Oliveira (2021)
Somatic resource banks play a crucial role in the conservation of genetic diversity, allowing the conservation of biological samples from different populations. Puma somatic cells can be recovered from these banks and used in assisted techniques to promote their multiplication and conservation. In response to the reduction in the population of this species of ecological importance, the present study aimed to evaluate the damages caused by cryopreservation in the formation of somatic tissue banks (Step 1), as well as to characterize cell lines after prolonged culture and cryopreservation (Step 2). For this purpose, fragments of the ear derived from four pumas kept in zoos in the city of Fortaleza, Ceará, were distributed in two stages. In the first stage, cryopreserved and non-cryopreserved fragments were evaluated for skin and cartilage thickness, number of cells, number of perinuclear halos, percentage of collagen matrix, and tissue proliferative activity. Moreover, cells resulting from the cultured fragments were evaluated for morphology, adherence, confluence, viability, proliferative activity, metabolic activity, oxidative stress, and levels of apoptosis. In the second stage, cells characterized as fibroblasts by immunocytochemistry were evaluated for the culture period (first, third and tenth passage) and effects of cryopreservation on morphology, ultrastructure, viability, proliferative activity, metabolism, levels of reactive oxygen species (ROS), mitochondrial membrane potential (ΔΨm) and levels of apoptosis. In the first stage, cryopreservation increased the thickness of the corneum layer in the tissues and the number of perinuclear halos and empty gaps. Despite this, cryopreservation was able to maintain normal fibroblast patterns, even with an increase in the percentage of collagen fibers. Additionally, cryopreservation maintained the proliferative potential of the tissues and parameters evaluated during in vitro culture, mainly regarding viability, proliferative activity, and levels of apoptosis. Nevertheless, cells of cryopreserved tissues showed decreased metabolism and ΔΨm. In the second stage, the cells showed a typical spindle-shaped morphology with centrally located oval nuclei. The cells were identified as fibroblasts by staining with vimentin. In vitro culture after the first, third and tenth pass did not change most of the evaluated parameters. The cells in the third and tenth pass showed a reduction in ROS levels (P < 0.05). The ultrastructure revealed morphological damage in the extensions and nuclei of cells derived from the third and tenth passages. Also, cryopreservation resulted in a reduction in ΔΨm compared to non-cryopreserved cells. In conclusion, puma somatic tissues submitted to cryopreservation are viable and maintain the integrity of the tissue, with minimal changes after warming. Additionally, viable fibroblasts can be obtained from somatic tissues of the puma ear, with minor changes after the tenth passage of in vitro culture and cryopreservation